NILAI EKONOMI DESTINASI WISATA MINAT KHUSUS KEE PULAU MASAKAMBING BERBASIS CONTINGENT VALUATION METHOD - Musyafak Musyafak; Ihsannudin Ihsannudin (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
The determination of Masakambing Island as an Essential Ecosystem Area (KEE) was motivated by the existence of endemic animals such as the Yellow-crested Little Cockatoo which needs to be conserved. This conservation is needed within the ecotourism activities. The appropriate ecotourism planning requires an economic assessment of an ecotourism destination. This study aims to determine the economic value of the KEE ecotourism destination of Masakambing Island and the factors that influence it. The approach used is the Willingness to Pay (WTP) with the Contingent Valuation Method (CVM). The results show that the economic value of Masakambing Island KEE is IDR 28,364,167/individual. The cumulative value of the economic value of Masakambing Island KEE is IDR 1,276,387,515/year. The factor that significantly influence is the cost incurred by visitors. This condition implies the need to improve the quality of attraction content in order to increase the value of its services. The potential for cultural attraction that is minimalist can be further developed towards local cultural performance event.Keywords: Cockatoos, CVM, Ecotourism, Masakambing, WTP